Treatment of compost as a source of organic material for bacterial consortium in the removal of sulfate and heavy metal lead (Pb) from acid mine drainage - Fahruddin Fahruddin; Nursiah La Nafie; Asadi Abdullah; Mustika Tuwo; Awaluddin Awaluddin (Journal of Degraded and Mining Lands Management, 2021)
Acid mine drainage can pollute the environment because it is acidic and contains toxic heavy metals. The purpose of this research was the application of a bacterial consortium to remove sulfate and reduce heavy metal lead (Pb) in acid mine drainage. The application was done in the bioreactor for acid mine drainage treatment that was treated with compost. Observations were made every five days and included observation of total bacterial growth using the Standard Plate Count (SPC) method, determination of sulfate content by gravimetry, determination of pH by use of pH meter, and determination of the concentration of heavy metal Pb using the AAS method. As a result, it was obtained that the treatment of non-sterile compost in acid mine drainage was able to reduce the initial heavy metal concentration of Pb of 84% and reduce the sulfate content by 72%, along with increasing pH and an increase in total bacterial growth. Meanwhile, sterile compost treatment was only able to reduce the Pb content by 63% and sulfate by 54%. This result indicates that the addition of compost is more effective than the treatment of sterile compost.